Effects of eccentric cycle ergometry in Alpine skiers - Gross, M.; Lüthy, F.; Kroell, J.; Müller, E.; Hoppeler, H.; Vogt, M. (International Journal of Sports Medicine, 2010)
Eccentric cycling, where the goal is to resist the pedals, which are driven by a motor, increases muscle strength and size in untrained subjects. We hypothesized that it could also be beneficial for athletes, particularly in alpine skiing, which involves predominantly eccentric contractions at longer muscle lengths. We investigated the effects of replacing part of regular weight training with eccentric cycling in junior male alpine skiers using a matched-pair design. Control subjects (n=7) executed 1-h weight sessions 3 times per week, which included 4-5 sets of 4 leg exercises. The eccentric group (n=8) performed only 3 sets, followed by continuous sessions on the eccentric ergometer for the remaining 20 min. After 6 weeks, lean thigh mass increased significantly only in the eccentric group. There was a group×time effect on squat-jump height favouring the eccentric group, which also experienced a 6.5% improvement in countermovement-jump height. The ability to finely modulate muscle force during variable eccentric cycling improved 50% (p=0.004) only in the eccentric group. Although eccentric cycling did not significantly enhance isometric leg strength, we believe it is beneficial for alpine skiers because it provides an efficient means for hypertrophy while closely mimicking the type of muscle actions encountered while skiing.